Pengaruh Diskon dan Gratis Ongkir Terhadap Keputusan Pembelian Mahasiswa Pada Aplikasi Shopee - Siska Lusia Putri; Rahmat Zulkifli (New Economy, 2025)
This research aims to determine the effect of discounts and free shipping on purchasing decisions. The population used in this research is undergraduate management and tourism undergraduate majors, economics and business faculty, Dharma Andalas University. This research used 109 respondents, using the Roasoft formula as a sampling technique. Hypothesis testing in this research uses statistical analysis consisting of validity test, reliability test, classic assumption test, t test, F test (hypothesis test) and multiple determination coefficient (R2) using SPSS (Statistics Product and Service Solution) software version 25. Research data comes from primary data and is taken by distributing questionnaires. The results of this research show that discounts have a significant influence on purchasing decisions, while free shipping has a significant influence on purchasing decisions. Simultaneously, all variables, namely Discounts and Free Shipping, have a significant influence on Student Purchasing Decisions (S1 Management and S1 Tourism Studies, Faculty of Economics and Business, Dharma Andalas University).